Characterization of a nanocrystalline Mg–Ni alloy processed by high-pressure torsion during hydrogenation and dehydrogenation. (22nd June 2016) - Gajdics, Marcell; Calizzi, Marco; Pasquini, Luca; Schafler, Erhard; Révész, Ádám
Abstract: Ball-milled Mg-Ni powder has been cold-compacted and subsequently processed by severe shear deformation under high-pressure torsion. The effect of high pressure torsion on morphology and microstructure of the disk-shape samples has been characterized by scanning electron microscopy and X-ray diffraction, respectively. In order to achieve partially hydrogenated and dehydrogenated states of deformed samples, the hydrogen uptake or release was interrupted at 25%, 50% and 75% hydrogen contents in a Sieverts' type apparatus. In this paper we present the characterization of the microstructure during a full absorption-desorption cycle of the nanocrystalline Mg–Ni alloy. Highlights: Mg2 Ni powders were subjected to high pressure torsion. Partial hydrogenation and dehydrogenation states were obtained. Microstructure was monitored during hydrogen cycling. Nanostructure is preserved during the entire hydrogenation–dehydrogenation process.